Book review: Blöchlinger H. 2023: Die Wollschweber der Schweiz. Diptera: Bombyliidae. Fauna Helvetica 34. - M. SEMELBAUER (European Journal of Entomology)
Blöchlinger H. 2023: Die Wollschweber der Schweiz. Diptera: Bombyliidae. Fauna Helvetica 34. Centre suisse de cartographie de la faune, Neuchâtel, 166 pp., 215 figs, 40 distribution maps. ISSN 1422-6367, ISBN 978-2-88414-047-8. Price CHF 50.00. Bilingual German/French.